Concise Chemical Synthesis of the Tetrasaccharide Repeating Unit of the O-Antigen from Bovine Mastitis Isolate E. coli Serotype O174:H28 - Mitra, Ankita; Mukhopadhyay, Balaram (Synthesis, 2015)
A concise strategy for the chemical synthesis of the tetrasaccharide repeating unit of the O-antigen from E. coli O174:H28 is reported. Synthesis of the target structure is accomplished by sequential glycosylation of rationally protected monosaccharide synthons derived from commercially available sugars. Glycosylation reactions were achieved by the activation of the thioglycosides using N-iodosuccinimide in the presence of H2SO4–silica. The carboxylic acid moiety of the glucuronic acid unit was successfully installed by a late TEMPO-mediated oxidation of the primary hydroxy group. Phthalimido groups were successfully used as the precursors of the required acetamido functionalities for 1,2-trans-glycosylations.
Keywords: bacterial O-antigen; acetamido sugars; H2SO4–silica